Predictors of Successful Outcome following Intrastromal Corneal Ring Segments Implantation. (3rd July 2019) - Sedaghat, Mohammad-Reza; Momeni-Moghaddam, Hamed; Piñero, David P.; Akbarzadeh, Reyhaneh; Moshirfar, Majid; Bamdad, Shahram; Gazanchian, Mehrdad
ABSTRACT: Purpose : To assess the preoperative visual, refractive, corneal topo/tomographic, aberrometric and biomechanical parameters as predictive factors of a successful outcome 6 months following intrastromal corneal ring segments implantation. Methods : Sixty-eight keratoconus eyes implanted with Keraring using femtosecond laser technology were assessed. The preoperative assessed parameters included uncorrected and corrected distance visual acuity (UDVA & CDVA), refraction, placido-disk based topography using TMS-4, Scheimplfug tomography using Pentacam HR, corneal biomechanical assessments using Ocular Response Analyzer (ORA) and the wavefront analysis using i-Trace aberrometer. Other variables were type of astigmatism based on orientation of the steep meridian, keratoconus staging based on the Amsler–Krumeich classification and the difference between the axes of refractive astigmatism, topographic astigmatism and comatic aberration based on a difference less or more than 30°. The success criterion was defined based on CDVA, a post-operative CDVA improvement at least two lines were considered as a success and otherwise were recognized as a failure following Keraring implantation. Results : Only UDVA, coincidence of the most elevated points on the front and back corneal surfaces and the difference between UDVA and CDVA showed significant difference between the eyes with successful outcomes and those with unsuccessful results ( P < 0.05). Although corneal curvature and astigmatism were higher and corneal thickness was lower in the unsuccessful group, differences were not statistically significant. Conclusion : It is expected that the greater difference between the preoperative uncorrected and corrected distance visual acuity (Δ UDVA–CDVA) and more coincidence of the most elevated points in the two corneal surfaces on the elevation maps increase the rate of successful outcome following the Keraring implantation. Abbreviations: ICRS: intrastromal corneal ring segments; UDVA: uncorrected distance visual acuity; CDVA: corrected distance visual acuity; logMAR: logarithm of minimum angle of resolution; SE: spherical equivalent; IOP: intra-ocular pressure; Km: mean keratometry; CA: corneal astigmatism; WTR: with-the-rule; ATR: against-the-rule; OBL: oblique; SB: symmetric bow-tie; AB: asymmetric bow-tie; IS: inferior steepening; SRAX: skewed radial axis; Q: asphericity ( Q -value); CCT: central corneal thickness; CTP: corneal thinnest point; ORA: ocular response analyzer; CH: corneal hysteresis; CRF: corneal resistance factor; HOAs: higher-orders aberrations; RMS: root mean square; SD: standard deviation; CI: confidence interval.